Tocando os Estribos: a equoterapia como intervenção na interação social de crianças com transtorno do espectro autista - Silva, Alberto Pereira da (2022)
Equine-assisted therapy is a complex multidisciplinary method, which can contribute to the improvement of psychomotor disabilities, interpersonal relationships and reduction of stereotyped patterns. Initially aimed at assisting people with disabilities, it may also be proposed to help the social interaction of children diagnosed with the autistic spectrum disorder (ASD). ASD manifests itself in the first years of life, with characteristic symptoms being observed around 18 months of age and more precisely diagnosed after the age of three. It presents itself in different levels, and is characterized mainly by communication deficits and difficulty in social interactions, with repetitive and restricted behavior patterns and often associated with developmental delays. The developmental perspective, when discussing the development of social interactions, highlights the importance of nonverbal behaviors and body expressions present in shared attention (CA) gestures, which may be present before spoken language. Considering the literature on intervention with the participation of horses, better known in Brazil as horseback riding, the aim of this study was to analyze the social interaction of practitioners diagnosed with ASD, aged between three and five years, participating in a horseback riding program. To this end, the interaction and the development of CA behaviors by the children during the sessions were recorded, as well as the perception of caregivers regarding the proposed intervention. With a descriptive design, the research was carried out through a multiple case study, with the participation of nine children diagnosed with ASD, aged between three and five years, practitioners in the Equine Therapy Social Program of the Military Police of Espírito Santo (PMES) and their guardians/caregivers. The following were used as pre- and post-intervention assessment instruments and to substantiate the intervention (a) Anamnesis Forms, (b) Childhood Autism Rating Scale (CARS), (c) Pictorial Infant Communication Scale (PICS), (d) Evaluation For Caregivers Sheets, (e) Script to guide the realization of the horseback riding sessions, and (f) Protocol for analysis of the sessions, which presented development levels referring to social orientation and CA, being also registered the expected behaviors in the interaction of the practitioner with the team and with the horse. The analysis of the results showed that all practitioners obtained better scores in the PICS and CARS in the moment after the intervention, compared to the previous moment: In the PICS assessment, all obtained improvement in the Total score and in the sub-score Initiation of Shared Attention; eight presented improvement in the sub-score Initiation of Soliciting Behavior; and four obtained advances in the sub-score Response to Shared Attention, with two obtaining the maximum score in both assessments. In the CARS evaluation, again all practitioners reached better scores in the final evaluation, however, only for one practitioner this change in score also translated into a change in the classification of the disorder, going from severe to mild/moderate. Regarding behaviors related to social interaction, the children showed changes mainly in those that originated from the spontaneous ability to signal to a social partner their interest, using gestures or directing their gaze. The behaviors were categorized according to their manifestation in the equine therapy sessions, within the categories: Absent; Triggered by the Caregiver; Triggered by the Mediator; Spontaneous. The Levels of development present in the analysis were described in two levels: I, subdivided into A and B; II, also subdivided into A and B. Finally, the categories of the interviews with the parents - Initial expectation; Acceptance of the horse's presence; Observed difficulties; Interest in the activity; Changes in the practitioner's behavior - show that they noticed an improvement in the practitioners' social interaction, whether in the family or in other contexts, and also the importance of the relationship between children, horses and the assistance team. It was concluded that CA behaviors, especially those related to social orientation, can be facilitated in the equine-assisted therapy environment, due to the characteristics of the intervention, which encourages interaction, initially between the practitioner and the horse, extending to the team. It was also observed that caregivers play an important role, especially in the adaptation during the initial period of the intervention and also that they notice the evolution of practitioners, especially in aspects related to social relationships and independence. The role of professional mediators is a primordial factor for the evolution of practitioners, through the encouragement of observed behaviors and management of the characteristics that the horse provides in the proposed activities. Equine-assisted therapy, therefore, offered a favorable environment for the stimulation and motivation of participants with ASD, being necessary the constant monitoring of the activity by the multidisciplinary team, so that the practitioner is the protagonist in his process in therapy.